Validation of a new tool for automatic assessment of tremor frequency from video recordings - Uhríková, Zdenka; Sprdlík, Otakar; Hoskovcová, Martina; Komárek, Arnošt; Ulmanová, Olga; Hlaváč, Václav; Nugent, Chris D; Růžička, Evžen (Journal of neuroscience methods, 2011)
We present a validation study for TremAn--a tool for automatic detection of tremor and measurement of its frequency from video recordings. To assess the validity of TremAn we designed a study consisting of tremor assessment from video, by accelerometry and by clinical evaluation using Fahn-Tolosa-Marin scale. 26 patients with essential tremor and 5 healthy volunteers underwent the examination in four standardized positions with focus on the hand tremor. Results showed that the frequencies of tremor measured with TremAn and with accelerometry are closely related, attaining agreement with less than 0.1 Hz difference in 80% and less than 0.5 Hz in 94% of measured samples. The reproducibility of frequency measurements using TremAn was comparable to the accelerometry, with the TremAn/accelerometry ratio of measurement error standard deviations equal to 0.99 (95% confidence interval (0.84, 1.17)).
Keywords: dospělí; funkční lateralita; Female; Functional Laterality; Adult; mladý dospělý; ženské pohlaví; Reproducibility of Results; lidé; tremor; Aged, 80 and over; stupeň závažnosti nemoci; Video Recording; Tremor; reprodukovatelnost výsledků; spektrální analýza; Male; Aged; Young Adult; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; audiovizuální záznam; Severity of Illness Index; Middle Aged; Spectrum Analysis; Humans